1976
DOI: 10.1139/x76-065
|View full text |Cite
|
Sign up to set email alerts
|

Variation in diameter of central columns of discoloration in six hybrid poplar clones

Abstract: The percentage of stem diameter discolored in the center of hybrid poplar logs varied by clones. For the six clones studies, discoloration columns ranged in percentage of total stem diameter from 85.0 to 55.8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The relative extent of discoloration associated with both branch and trunk wounds was not significantly correlated to closure rate. This is in agreement with the work of Shigo et al (2,6), which indicates the existence of 2 separate and basically unre lated processes: closure and compartmentalization.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The relative extent of discoloration associated with both branch and trunk wounds was not significantly correlated to closure rate. This is in agreement with the work of Shigo et al (2,6), which indicates the existence of 2 separate and basically unre lated processes: closure and compartmentalization.…”
Section: Resultssupporting
confidence: 93%
“…Hepting et al (3) observed that the extent of wound-associated discoloration was relatively consistent within a species. Shigo et al (2,6) demonstrated surprisingly large differences regarding the ability of a clone within the species to compartmentalize rapidly and effectively. Degree of compartmentalization was found to be consistent within a clone, unrelated to closure rate, independent of growth rate, and not a function of tree size.…”
mentioning
confidence: 99%
“…Similar results for the same species were presented by Wang et al [25] in a study where the poplars were planted in spacings of 2 × 5, 4 × 5 and 4 × 10 m wetwood represented 56%, 62% and 65% of total volume respectively. In a study of six hybrid poplar clones, Garret et al [36] found different percentages of discolored wood versus stem diameter in logs.…”
Section: Characteristics Of the Distribution Of False Heartwood In Stemsmentioning
confidence: 99%